2011
DOI: 10.1073/pnas.1016048108
|View full text |Cite
|
Sign up to set email alerts
|

Immune escape from HIV-specific antibody-dependent cellular cytotoxicity (ADCC) pressure

Abstract: Effective immunity to HIV is poorly understood. In particular, a role for antibody-dependent cellular cytotoxicity (ADCC) in controlling HIV is controversial. We hypothesized that significant pressure from HIV-specific ADCC would result in immune-escape variants. A series of ADCC epitopes in HIV-infected subjects to specific consensus strain HIV peptides were mapped using a flow cytometric assay for natural killer cell activation. We then compared the ADCC responses to the same peptide epitope derived from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
132
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 25 publications
2
132
0
1
Order By: Relevance
“…By reducing the accumulation of virions of the cell surface, Vpu may lower the sensitivity of HIV-infected cells to antibodies, facilitating ongoing virus replication and immune escape. Partial resistance to ADCC is consistent with evidence that antibodies capable of directing ADCC may select for immune escape variants (43). In this regard, Vpu-mediated resistance to ADCC is perhaps analogous to Nefmediated resistance to cytotoxic T lymphocytes (CTLs), in which MHC class I down-regulation by Nef reduces, but does not eliminate, CD8 + T-cell recognition of HIV-infected cells, as reflected by the well-documented emergence of CTL escape variants (44).…”
Section: Discussionmentioning
confidence: 64%
“…By reducing the accumulation of virions of the cell surface, Vpu may lower the sensitivity of HIV-infected cells to antibodies, facilitating ongoing virus replication and immune escape. Partial resistance to ADCC is consistent with evidence that antibodies capable of directing ADCC may select for immune escape variants (43). In this regard, Vpu-mediated resistance to ADCC is perhaps analogous to Nefmediated resistance to cytotoxic T lymphocytes (CTLs), in which MHC class I down-regulation by Nef reduces, but does not eliminate, CD8 + T-cell recognition of HIV-infected cells, as reflected by the well-documented emergence of CTL escape variants (44).…”
Section: Discussionmentioning
confidence: 64%
“…Prevention of HIV-1 transmission and progression likely requires approaches that can specifically target and eliminate HIV-1-infected cells. Interestingly, there is increasing evidence supporting a role of antibody (Ab)-dependent cellmediated cytotoxicity (ADCC) in controlling HIV-1 transmission and disease progression (2)(3)(4)(5)(6)(7)(8). Analysis of the correlates of protection in the RV144 vaccine trial suggested that increased ADCC activity was linked with decreased HIV-1 acquisition (9), and Abs with potent ADCC activity were isolated from some RV144 vaccinees (10).…”
mentioning
confidence: 99%
“…7 Other recent studies supporting a role for ADCC in host defense against HIV include evidence of its ability to prevent HIV transmission through breastfeeding, 8 confirmation that ADCC killing correlates inversely with viral load, 9 and the suggestion that ADCC exerts immune pressure on HIV replication. [10][11][12] If ADCC antibodies are an important part of the immune defense against HIV, it is important to determine whether HIV vaccines that are designed to stimulate an ADCC response against HIV will work equally well in men and in women.…”
mentioning
confidence: 99%